Method for manufacturing rare earth magnet

CN116895462BActive Publication Date: 2026-11-03TOYOTA JIDOSHA KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310328737.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-03-31
Filing Date
2023-03-30
Publication Date
2026-11-03
Estimated Expiration
2043-03-30

AI Technical Summary

Technical Problem

Existing technologies struggle to stably impart sufficient anisotropy to Sm-Fe-N rare-earth magnets during pressure sintering, leading to a tendency for the magnetic orientation of the magnetically shaped body to collapse.

Method used

A magnetic field is applied to the raw material powder before pressure sintering and continues to be applied during the pressure sintering process to maintain magnetic orientation. Magnetic fields are applied in different directions of pressure application using permanent magnets.

Benefits of technology

By applying a continuous magnetic field, Sm-Fe-N rare earth magnets can be stably endowed with sufficient anisotropy, thereby improving the magnetic orientation stability of the magnets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116895462B_ABST
    Figure CN116895462B_ABST
Patent Text Reader

Abstract

The present disclosure is a manufacturing method of a rare-earth magnet. The present disclosure provides a manufacturing method of a Sm-Fe-N-based rare-earth magnet capable of stably imparting sufficient anisotropy. The manufacturing method of a rare-earth magnet of the present disclosure includes the following steps: preparing a raw material powder containing a magnetic powder (SmFeN powder (10)) containing Sm, Fe, and N and having a magnetic phase having at least any one of a Th2Zn 17 type and a Th2Ni 17 type; and pressure-sintering the raw material powder. In the manufacturing method, a magnetic field is applied to the raw material powder to impart a magnetic orientation before the pressure-sintering, and the magnetic orientation is maintained by continuing the application of the magnetic field until at least the middle of the pressure-sintering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to a method for manufacturing rare earth magnets. In particular, this disclosure relates to magnets containing Sm, Fe, and N, and having at least a portion of Th₂Zn. 17 Type and Th2Ni 17 A method for manufacturing rare earth magnets of at least one of the magnetic phases with a crystal structure in the type. Background Technology

[0002] Sm-Co and Nd-Fe-B rare earth magnets have been put into practical use as high-performance rare earth magnets, but in recent years, research has been conducted on rare earth magnets other than these.

[0003] For example, research is underway on rare-earth magnets containing Sm, Fe, and N (hereinafter sometimes referred to as "Sm-Fe-N rare-earth magnets"). Sm-Fe-N rare-earth magnets are manufactured, for example, using magnetic powders containing Sm, Fe, and N (hereinafter sometimes referred to as "SmFeN powder").

[0004] SmFeN powder possesses at least a portion of Th2Zn. 17 Type and Th2Ni 17 The magnetic phase is defined as having at least one crystal structure in the Sm-Fe type. This magnetic phase is considered to be N dissolved in the Sm-Fe crystal in an interstitial form. Therefore, SmFeN powder is easily decomposed by thermal separation of N. Consequently, Sm-Fe-N rare earth magnets are often manufactured by molding SmFeN powder using resin and / or rubber.

[0005] Another method for manufacturing Sm-Fe-N rare-earth magnets besides this is the pressure sintering of powder containing SmFeN powder. Sintering methods are broadly classified into pressureless sintering and pressure sintering. Both methods obtain high-density rare-earth magnets (sintered bodies) through sintering. In pressureless sintering, no pressure is applied to the magnetic powder during sintering; therefore, to obtain a high-density sintered body, sintering is generally performed at a high temperature of 900°C or higher for a long time of 6 hours or more. On the other hand, in pressure sintering, pressure is applied to the magnetic powder during sintering; therefore, even at a low temperature of 400–700°C and a short sintering time of 0.1–5 hours, a high-density sintered body can generally be obtained. Therefore, when using SmFeN powder as the magnetic powder, pressure sintering is used to avoid the aforementioned decomposition.

[0006] It is known that when SmFeN powder is formed, in order to impart anisotropy to the sintered body under pressure sintering, the powder containing SmFeN powder is compressed and formed in a magnetic field before pressure sintering to obtain a magnetically formed body, and the magnetically formed body is then subjected to pressure sintering.

[0007] For example, Patent Document 1 discloses a method for obtaining a magnetically shaped body by compressing a powder containing SmFeN powder with a permanent magnet. In this specification, unless otherwise specified, the process of compressing magnetic powder in a magnetic field to obtain a pressed powder body is referred to as "magnetically shaped body", and the pressed powder body obtained by magnetic field shaping is referred to as "magnetically shaped body".

[0008] Prior art literature

[0009] Patent documents

[0010] Patent Document 1: Japanese Patent Application Publication No. 2021-141121 Summary of the Invention

[0011] Because SmFeN powder has a very high anisotropic magnetic field, it is believed that a strong magnetic field needs to be applied to the SmFeN-containing powder in order to achieve sufficient magnetic orientation in the magnetically formed body. However, even when the magnetically formed body is subjected to pressure sintering with a strong magnetic field, the desired anisotropy is sometimes not obtained.

[0012] The method in Patent Document 1 aims to perform magnetic field forming using a simple apparatus at a high temperature where the magnetic phase in SmFeN powder does not decompose. This is because it is believed that at a high temperature where the magnetic phase in SmFeN powder does not decompose, the anisotropic magnetic field of SmFeN powder decreases, which is advantageous for magnetic field forming. However, in the method of Patent Document 1, even when performing magnetic field forming at a high temperature where the magnetic phase in SmFeN powder does not decompose, and then pressurizing and sintering the resulting magnetically formed body, the desired anisotropy is sometimes not obtained.

[0013] This disclosure was made to solve the aforementioned problems. Specifically, the purpose of this disclosure is to provide a method for manufacturing Sm-Fe-N rare-earth magnets that can stably impart sufficient anisotropy.

[0014] To achieve the above objectives, the inventors conducted repeated and in-depth research and completed the method for manufacturing rare earth magnets disclosed herein. The method for manufacturing rare earth magnets disclosed herein includes the following steps.

[0015] <1> A method for manufacturing a rare earth magnet, comprising the following steps:

[0016] Prepare a raw material powder containing magnetic powder, wherein the magnetic powder contains Sm, Fe and N and has at least a portion of Th2Zn. 17 Type and Th2Ni 17At least one magnetic phase with a crystal structure in the type; and

[0017] The raw material powder is then subjected to pressure sintering.

[0018] Before the pressure sintering, a magnetic field is applied to the raw material powder to impart magnetic orientation, and...

[0019] The magnetic field is continuously applied to maintain the magnetic orientation until at least the end of the pressure sintering process.

[0020] <2> According to the method for manufacturing rare earth magnets described in <1>, the magnetic field is applied in a direction different from the pressure direction of the pressure sintering.

[0021] <3> The magnetic field is applied using a permanent magnet according to the manufacturing method of the rare earth magnet described in <1> or <2>.

[0022] <4> The method for manufacturing rare earth magnets according to any one of <1> to <3> further comprises a powder containing zinc.

[0023] <5> The method for manufacturing rare earth magnets according to any one of <1> to <4> forms a coating having a zinc component on the surface of the magnetic powder particles.

[0024] <6> The method for manufacturing rare earth magnets according to any one of <1> to <5> involves compressing the raw material powder to form a pressed powder body while applying the magnetic field before the pressure sintering, and then subjecting the pressed powder body to pressure sintering.

[0025] <7> The method for manufacturing rare earth magnets according to any one of <1> to <6> continues to apply the magnetic field to maintain the magnetic orientation until the pressure sintering is completed.

[0026] According to this disclosure, by continuously applying a magnetic field to a raw material powder containing SmFeN powder, which has been magnetically oriented by applying a magnetic field, and simultaneously performing pressure sintering, the magnetic orientation of the SmFeN powder can be maintained. As a result, according to this disclosure, a method for manufacturing Sm-Fe-N based rare-earth magnets that can stably acquire sufficient anisotropy can be provided. Attached Figure Description

[0027] Figure 1 This is an illustrative diagram schematically representing the magnetic state of SmFeN powder before a magnetic field is applied.

[0028] Figure 2 This is an illustrative diagram schematically representing the magnetic state of SmFeN powder under an applied magnetic field.

[0029] Figure 3 This is a schematic diagram illustrating the magnetic state of SmFeN powder after the magnetic field is removed from the magnetic field, which has been magnetically oriented by the applied magnetic field.

[0030] Figure 4 This is a schematic diagram illustrating the magnetic field emitted by a rod-shaped permanent magnet.

[0031] Figure 5 This is an illustrative diagram illustrating an example of a method for forming a zinc-containing film on the particle surface of SmFeN powder using a rotary kiln furnace.

[0032] Figure 6 This is an illustrative diagram illustrating an example of a method for forming a zinc-containing film on the surface of SmFeN powder particles using a vapor deposition process.

[0033] Figure 7 This is an explanatory diagram illustrating an example of a method for applying a magnetic field.

[0034] Figure 8 This is an explanatory diagram showing an example of the direction in which a magnetic field is applied.

[0035] Explanation of reference numerals in the attached figures

[0036] 10SmFeN powder

[0037] 20 rod-shaped permanent magnets

[0038] 30 Magnetic Field Generators

[0039] 100 rotary kiln

[0040] 110 Stirring drum

[0041] 120 Material Storage Department

[0042] 130 rotating shaft

[0043] 140 mixing plate

[0044] 150SmFeN powder

[0045] 160 Powder containing zinc

[0046] 171 First Heat Treatment Furnace

[0047] 172 Second Heat Treatment Furnace

[0048] 173 Connector Road

[0049] 180 vacuum pump

[0050] 181 First Container

[0051] 182 Second Container Detailed Implementation

[0052] The following provides a detailed description of the embodiments of the rare-earth magnet manufacturing method of this disclosure. Furthermore, the embodiments shown below do not limit the manufacturing method of the rare-earth magnet of this disclosure.

[0053] Although not bound by theory, the accompanying drawings are used to explain why the manufacturing method of rare earth magnets according to this disclosure can stably impart sufficient anisotropy to rare earth magnets (products).

[0054] Figure 1 This is an illustrative diagram schematically representing the magnetic state of SmFeN powder before a magnetic field is applied. Figure 2 This is an illustrative diagram schematically representing the magnetic state of SmFeN powder under an applied magnetic field. Figure 3 This is a schematic diagram illustrating the magnetic state of SmFeN powder after the magnetic field is removed, following the removal of the applied magnetic field from the powder that has been magnetically oriented under a magnetic field. Figures 1-3 In the image, the solid arrows indicate the magnetic orientation of each SmFeN powder particle. Additionally, Figure 4 This is a schematic diagram illustrating the magnetic field emitted by a rod-shaped permanent magnet.

[0055] like Figure 1 As shown, before the magnetic field is applied, the particles of SmFeN powder 10 have no magnetic orientation. If a magnetic field is applied to SmFeN powder in this state, then... Figure 2 As shown, the particles of SmFeN powder 10 are magnetically oriented along the direction of the applied magnetic field. Figure 2 In the diagram, the dashed arrows indicate the direction of the magnetic field applied to the SmFeN powder 10. At this point, the entire SmFeN powder 10 becomes a rod-shaped permanent magnet. (As shown...) Figure 4 As shown, the rod-shaped permanent magnet 20 forms the magnetic field indicated by the solid arrow. If the applied magnetic field to the SmFeN powder 10 is maintained, it is easily counteracted. Figure 4 The magnetic field, represented by solid lines, is that each particle of SmFeN powder 10 can maintain its own magnetic field. Figure 2 The magnetic orientation is shown in the figure.

[0056] However, if the magnetic field is removed, then as Figure 3 As shown, the individual magnetic orientations of the SmFeN powder 10 particles collapse. This is because: due to the overall formation of the oriented SmFeN powder 10... Figure 4 The magnetic field, represented by the solid arrow in the image, is like that of a rod-shaped permanent magnet, and thus becomes applied to each particle of the SmFeN powder 10. Figure 3 The same state applies to the magnetic field represented by the dashed line in the diagram. In the following description, sometimes... Figure 3The magnetic field represented by a single-dot dash in the image is called the "magnetic field formed by the entire SmFeN powder".

[0057] To avoid the aforementioned collapse of magnetic orientation, the residual magnetic force in the SmFeN powder can be removed by alternating current (AC) demagnetization. However, AC demagnetization takes time. Furthermore, even with AC demagnetization, it is difficult to completely remove the residual magnetic force from the SmFeN powder. Even if AC demagnetization completely removes the residual magnetic force, a small but persistent magnetic field is generated throughout the entire SmFeN powder before the removal is complete. Therefore, it is difficult to completely avoid the aforementioned collapse of magnetic orientation.

[0058] Then, the inventors discovered that in order to prevent the individual orientations of SmFeN powder particles from collapsing due to the magnetic field formed by the entire SmFeN powder particle group, the magnetic field should be continuously applied until the SmFeN powder particles bond together. This is because the bonding force between the SmFeN powder particles suppresses the rotation of the temporarily oriented SmFeN powder particles caused by the magnetic field formed by the entire SmFeN powder group. The bonding of SmFeN powder particles occurs, if early, during the pressure sintering of the SmFeN powder, and at the latest, only after the pressure sintering of the SmFeN powder has ended. Therefore, the inventors discovered that the magnetic field should be continuously applied until at least during the pressure sintering of the SmFeN powder, preferably until the pressure sintering of the SmFeN powder has ended. Furthermore, this allows for the stable imparting of sufficient anisotropy to the sintered body.

[0059] In this specification, unless otherwise specified, the degree of orientation is calculated according to the following principles. In the magnetization-magnetic field curve, the magnetization (i.e., magnetization intensity) at a magnetic field of 1T is denoted as M(1T), and the magnetization at a magnetic field of 8T is denoted as M(8T). The degree of orientation is calculated by M(1T) / M(8T). When the magnetization at a magnetic field of 0T is set as M(0T), by omitting M(0T) in the above formula instead of M(1T), even in samples with very low coercivity, the degree of orientation can be evaluated even if the magnetization decreases to above the degree of orientation due to the influence of the self-reversing magnetic field (self-demagnetizing magnetic field).

[0060] The constituent elements of the method for manufacturing rare earth magnets disclosed herein, based on the insights and other information presented so far, will now be explained.

[0061] Manufacturing methods of rare earth magnets

[0062] The method for manufacturing rare earth magnets disclosed herein (hereinafter sometimes referred to as "the manufacturing method of this disclosure") includes a raw material powder preparation step and a pressure sintering step. Each step is described below.

[0063] <Raw Material Powder Preparation Process>

[0064] Prepare the raw material powder. The raw material powder contains SmFeN powder. The following is a description of the SmFeN powder.

[0065] 〈SmFeN powder〉

[0066] The SmFeN powder used in the manufacturing method of this disclosure contains Sm, Fe and N and has at least a portion of Th2Zn. 17 Type and Th2Ni 17 There are no particular restrictions on the magnetic phase having at least one crystal structure in the type. In addition to the structures mentioned above, crystal structures of the TbCu7 type can also be cited as examples of magnetic phases. Furthermore, Sm is samarium, Fe is iron, and N is nitrogen. Additionally, Th is thorium, Zn is zinc, Ni is nickel, Tb is terbium, and Cu is copper.

[0067] SmFeN powder may contain, for example, components of the formula (Sm... (1-i) R i )2(Fe (1-j) Co j ) 17 N h The magnetic phase is indicated. Rare-earth magnets (hereinafter sometimes referred to as "products") obtained using the manufacturing method of this disclosure exhibit magnetization originating from the magnetic phase in SmFeN powder. Furthermore, i, j, and h are molar ratios.

[0068] In the magnetic phase of SmFeN powder, R may be present within a range that does not impair the effectiveness of the manufacturing method disclosed herein or the magnetic properties of the product. Such a range is represented by i in the above composition formula. i can be, for example, 0 or more, 0.10 or more, or 0.20 or more, or 0.50 or less, 0.40 or less, or 0.30 or less. R is one or more rare earth elements selected from Sm and Zr. In this specification, rare earth elements are Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. Additionally, Zr represents zirconium, Sc represents scandium, Y represents yttrium, La represents lanthanum, Ce represents cerium, Pr represents praseodymium, Nd represents neodymium, Pm represents promethium, Sm represents samarium, Eu represents europium, Gd represents gadolinium, Tb represents terbium, Dy represents dysprosium, Ho represents holmium, Er represents erbium, Tm represents thulium, Yb represents ytterbium, and Lu represents lutetium.

[0069] Regarding (Sm) (1-i) Ri )2(Fe (1-j) Co j ) 17 N h As a typical example, R is substituted into Sm2(Fe). (1-j) Co j ) 17 N h The location of Sm is not limited to this. For example, a portion of R can also be configured in an interstitial manner in Sm2(Fe). (1-j) Co j ) 17 N h middle.

[0070] In the magnetic phase of SmFeN powder, Co may also be present within a range that does not impair the effectiveness of the manufacturing method disclosed herein or the magnetic properties of the product. Such a range is represented by j in the above composition formula. j can be 0 or more, 0.10 or more, or 0.20 or more, or 0.52 or less, 0.50 or less, 0.40 or less, or 0.30 or less.

[0071] Regarding (Sm) (1-i) R i )2(Fe (1-j) Co j ) 17 N h As a typical example, Co substitutes for (Sm (1-i) R i )2Fe 17 N h The location of Fe, but not limited to this. For example, a portion of Co can also be configured in an interstitial manner in (Sm (1-i) R i )2Fe 17 N h middle.

[0072] The magnetic phase in SmFeN powder exists in an interstitial form through N in the (SmFeN) powder. (1-i) R i )2(Fe (1-j) Co j ) 17 The indicated grains contribute to the manifestation and enhancement of magnetic properties.

[0073] Regarding (Sm) (1-i) R i )2(Fe (1-j) Co j ) 17 N h h can be 1.5 to 4.5, and typically it is (Sm (1-i) R i )2(Fe(1-j) Co j ) 17 N3. h can be 1.8 or higher, 2.0 or higher, or 2.5 or higher, and can be 4.2 or lower, 4.0 or lower, or 3.5 or lower. (Relative to Sm) (1-i) R i )2(Fe (1-j) Co j ) 17 N h Overall, (Sm (1-i) R i )2(Fe (1-j) Co j ) 17 The N3 content is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more. On the other hand, it may not be necessary to include (Sm) (1-i) R i )2(Fe (1-j) Co j ) 17 N h All of them are (Sm (1-i) R i )2(Fe (1-j) Co j ) 17 N3. Relative to (Sm) (1-i) R i )2(Fe (1-j) Co j ) 17 N h Overall, (Sm (1-i) R i )2(Fe (1-j) Co j ) 17 The N3 content can be below 98% by mass, below 95% by mass, or below 92% by mass.

[0074] SmFeN powder, except for (Sm (1-i) R i )2(Fe (1-j) Co j ) 17 N h In addition to the magnetic phase indicated, oxygen and M may be present within a range that does not substantially impair the effectiveness of the manufacturing method of this disclosure or the magnetic properties of the product. 1 And unavoidable impurity elements. From the point of view of ensuring the magnetic properties of the product, relative to the overall SmFeN powder, using (Sm (1-i) R i )2(Fe (1-j) Co j )17 N h The indicated magnetic phase content can be 80% by mass or more, 85% by mass or more, or 90% by mass or more. On the other hand, even without excessively increasing the content of (SmFeN) relative to the overall SmFeN powder... (1-i) R i )2(Fe (1-j) Co j ) 17 N h The indicated content of the magnetic phase is also practically acceptable. Therefore, its content can be below 97% by mass, below 95% by mass, or below 93% by mass. (Sm...) (1-i) R i )2(Fe (1-j) Co j ) 17 N h The remaining portion (balance) other than the magnetic phase represents oxygen and M. 1 The content of [unclear]. Additionally, oxygen and M [unclear]. 1 A portion of it may exist in the magnetic phase as interstitial and / or substitutional types.

[0075] As mentioned above, M 1 The following elements can be selected from one or more of Ga, Ti, Cr, Zn, Mn, V, Mo, W, Si, Re, Cu, Al, Ca, B, Ni, and C. Unavoidable impurity elements refer to those that cannot be avoided during the manufacture of raw materials and / or magnetic powders, or whose presence would significantly increase manufacturing costs if avoided. These elements may exist in the aforementioned magnetic phases as substitutional and / or interstitial elements, or in phases other than the aforementioned magnetic phases. Alternatively, they may exist at the grain boundaries of these phases. Furthermore, Ga represents gallium, Ti represents titanium, Cr represents chromium, Zn represents zinc, Mn represents manganese, V represents vanadium, Mo represents molybdenum, W represents tungsten, Si represents silicon, Re represents rhenium, Cu represents copper, Al represents aluminum, Ca represents calcium, B represents boron, Ni represents nickel, and C represents carbon.

[0076] There are no particular restrictions on the particle size of SmFeN powder as long as it does not hinder pressure sintering. The particle size of SmFeN powder is expressed in terms of D... 50 The size can be, for example, 1μm or more, 2μm or more, 3μm or more, 4μm or more, 5μm or more, 6μm or more, 7μm or more, 8μm or more, or 9μm or more, and can be less than 20μm, less than 19μm, less than 18μm, less than 17μm, less than 16μm, less than 15μm, less than 14μm, less than 13μm, less than 12μm, less than 11μm, or less than 10μm.

[0077] D of SmFeN powder 50The particle size distribution of SmFeN powder was calculated. Furthermore, the particle size distribution of SmFeN powder was determined (investigated) using the method described below. In this specification, unless otherwise specified, the description of the particle size (particle diameter) of SmFeN powder is based on the following determination method (investigation method). Furthermore, D 50 This refers to the median particle size (median diameter).

[0078] A sample was prepared by embedding SmFeN powder in resin. The surface of the sample was ground and observed using an optical microscope. Then, a straight line was drawn on the optical microscope image, and the length of the line segment divided by SmFeN particles (bright field of view) was measured. The particle size distribution of the SmFeN powder was determined from the frequency distribution of the line segment lengths. The particle size distribution obtained by this method is approximately equal to that obtained by the intersection method or dry laser diffraction-scattering method.

[0079] From the viewpoint of improving coercivity, the oxygen content of the SmFeN powder is preferably low relative to the overall SmFeN powder. The oxygen content of the SmFeN powder is preferably 2.0% by mass or less, more preferably 1.5% by mass or less, and even more preferably 1.0% by mass or less, relative to the overall SmFeN powder. On the other hand, drastically reducing the oxygen content in the SmFeN powder would lead to an increase in manufacturing costs. Therefore, the oxygen content of the SmFeN powder can be 0.1% by mass or more, 0.2% by mass or more, or 0.3% by mass or more, relative to the overall SmFeN powder.

[0080] If the conditions described above are met, there are no particular restrictions on the manufacturing method of SmFeN powder, and commercially available products can also be used.

[0081] In the manufacturing method of this disclosure, the raw material powder may contain zinc-containing powder in addition to SmFeN powder. By absorbing oxygen from the SmFeN powder with the zinc-containing powder, the magnetic properties, particularly the coercivity, of the finished product can be improved. Therefore, the oxygen content in the SmFeN powder can be determined by considering the amount of oxygen absorbed by the zinc-containing powder in the manufacturing process of this disclosure. Furthermore, the zinc-containing powder increases the bonding force between SmFeN powder particles, thereby further suppressing orientation breakdown of the SmFeN powder. The zinc-containing powder will be described below.

[0082] <Powder containing zinc>

[0083] The powder containing zinc typically contains at least one of metallic zinc and zinc alloys. Metallic zinc refers to unalloyed zinc. The zinc component binds and modifies the particles of the SmFeN powder. Furthermore, in the case where the SmFeN powder particles contain microparticles, the magnetic properties are improved by neutralizing these microparticles. Microparticles are defined as particles with a particle size of 1.0 μm or less.

[0084] By incorporating zinc into the powder, SmFeN powder particles can be more firmly bonded together. Furthermore, during pressure sintering, a portion of the zinc diffuses to the surface of the SmFeN powder particles, forming an Fe-Zn alloy phase. This results in Th₂Zn on the surface of the SmFeN powder particles. 17 Type and / or Th2Ni 17 In the incomplete crystal structure of certain types, the presence of an α-Fe phase contributes to reduced coercivity. This α-Fe phase combines with zinc to form an Fe-Zn alloy phase, suppressing the decrease in coercivity. Specifically, Fe and Zn diffuse between SmFeN powder particles and zinc-containing powder particles, forming an Fe-Zn alloy phase. In other words, the zinc-containing powder functions not only as a binder but also as a modifier.

[0085] Microparticles sometimes exist in SmFeN powder. Among these microparticles, Th₂Zn… 17 Type and / or Th2Ni 17 The proportion of incomplete crystal structures, such as those of the micronized particles, is high, resulting in a high proportion of the α-Fe phase. Therefore, the micronized particles contribute to the reduction of magnetic properties, particularly coercivity. During pressure sintering, most of the α-Fe phase originating from the micronized particles and the zinc-containing powder not only form an Fe-Zn alloy phase on the particle surface but also within the particle itself. Furthermore, it is believed that most of the Fe-Zn alloy phase originating from the micronized particles is integrated with the Fe-Zn alloy phase formed on the surface of larger SmFeN particles (particles other than micronized particles). Therefore, the zinc-containing powder neutralizes the micronized particles in terms of magnetic properties, particularly coercivity.

[0086] The zinc content in the raw material powder can be appropriately determined to advantageously perform its binder, modifier, and microparticle harmless functions. If the zinc content in the raw material powder is 1% or more by mass, 3% or more by mass, 6% or more by mass, 7% or more by mass, or 8% or more by mass relative to the total raw material powder, the aforementioned functions can be advantageously performed, and this is preferred. On the other hand, if the zinc content in the raw material powder is 30% or less by mass, 25% or less by mass, 20% or less by mass, 15% or less by mass, or 10% or less by mass relative to the total of SmFeN powder and zinc-containing powder, the decrease in magnetization caused by the use of zinc-containing powder can be suppressed, and this is also preferred.

[0087] As mentioned above, powders containing zinc typically contain at least one of metallic zinc and zinc alloys. When using Zn-M... 2 When referring to zinc alloys, M 2 Elements that allow alloying with Zn (zinc) to achieve a melting start temperature lower than the melting point of Zn, as well as unavoidable impurity elements, can be selected. This improves sinterability during the pressure sintering process. M is used to achieve the melting start temperature lower than the melting point of Zn. 2 Elements that can form eutectic alloys with Zn can be listed, such as M. 2 Typical examples include Sn, Mg, and Al, as well as combinations thereof. Sn is tin, Mg is magnesium, and Al is aluminum. Elements that do not impair the lowering of the melting point and the properties of the product caused by these elements can also be selected as M. 2 In addition, the so-called unavoidable impurity elements refer to impurities such as zinc-containing powder that cannot be avoided in the raw materials or whose presence would lead to a significant increase in manufacturing costs.

[0088] Using Zn-M 2 In the zinc alloy represented, Zn and M 2 The ratio (molar ratio) only needs to be determined appropriately to make the sintering temperature suitable. 2 The molar ratio relative to the total zinc alloy can be, for example, 0.05 or more, 0.10 or more, or 0.20 or more, or 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, or 0.30 or less.

[0089] Powders containing zinc, in addition to metallic zinc and / or zinc alloys, may optionally contain substances with binder and / or modifier functions, as well as other functions, without impairing the effects of the present invention. Examples of other functions include, for instance, improved corrosion resistance.

[0090] The particle size of the zinc-containing powder is not particularly limited, but it is preferably finer than that of the SmFeN powder. This allows the zinc-containing powder particles to easily disperse among the SmFeN powder particles. The particle size of the zinc-containing powder, for example, is expressed in terms of D... 50 The median particle size can be 0.1 μm or larger, 0.5 μm or larger, or 1.0 μm or larger, and can be 12.0 μm or smaller, 11.0 μm or smaller, 10.0 μm or smaller, 9.0 μm or smaller, 8.0 μm or smaller, 7.0 μm or smaller, 6.0 μm or smaller, 5.0 μm or smaller, 4.0 μm or smaller, or 2.0 μm or smaller. Additionally, the particle size D of the powder containing zinc is... 50 (Median particle size) can be determined, for example, by dry laser diffraction-scattering.

[0091] If the zinc-containing powder has a low oxygen content, it can absorb more oxygen from the SmFeN powder, which is preferable. From this point of view, the oxygen content of the zinc-containing powder, relative to the total amount of zinc-containing powder, is preferably 5.0% by mass or less, more preferably 3.0% by mass or less, and even more preferably 1.0% by mass or less. On the other hand, drastically reducing the oxygen content of the zinc-containing powder would lead to an increase in manufacturing costs. Therefore, the oxygen content of the zinc-containing powder, relative to the total amount of zinc-containing powder, can be 0.1% by mass or more, 0.2% by mass or more, or 0.3% by mass or more.

[0092] When the raw material powder contains zinc-containing powder in addition to SmFeN powder, there are no particular limitations on the mixing method of SmFeN powder and zinc-containing powder. Examples of mixing methods include using a mortar and pestle, a muller wheel mixer, an agitator mixer, a mechanofusion machine, a V-type mixer, and a ball mill. Combinations of these methods are also possible. Furthermore, a V-type mixer is a device that uses two cylindrical containers connected in a V-shape to form a container, and mixes the powder by repeatedly aggregating and separating the powder within the container due to gravity and centrifugal force through rotation.

[0093] It can also replace zinc-containing powder, or be used together with zinc-containing powder, to form a zinc-containing coating on part or all of the particle surface of SmFeN powder in the raw material powder. The zinc-containing coating is described below.

[0094] <Coating with zinc content>

[0095] A zinc-containing film can be formed on the surface of SmFeN powder particles in the raw material powder. This achieves the same effect as when the raw material powder contains zinc powder in addition to SmFeN powder.

[0096] Regarding the zinc-containing coating, it can be formed on the surface of a subset of SmFeN powder particles, or it can be formed on the surface of all SmFeN powder particles. "A zinc-containing coating is formed on the surface of a subset of SmFeN powder particles" means that a zinc-containing coating is formed on the surface of a subset of all SmFeN powder particles. "A zinc-containing coating is formed on the surface of all SmFeN powder particles" means that, for the SmFeN powder, a zinc-containing coating is formed on the surface of substantially all particles. "Substantially all particles" means that, depending on the method of forming the zinc-containing coating, there may inevitably be a very small number of particles that do not form a zinc-containing coating.

[0097] The formation of a zinc-containing coating on the surface of some or all of the SmFeN powder particles in the raw material powder can replace the zinc-containing powder or be used in conjunction with the zinc-containing powder. "Replacing the zinc-containing powder" means that the raw material powder substantially does not contain zinc-containing powder, and a zinc-containing coating is formed on the surface of some or all of the SmFeN powder particles. "Substantially does not contain" means that, during the preparation of the raw material powder, a very small amount of zinc-containing powder may unavoidably be present due to the apparatus, etc. Furthermore, "used in conjunction with zinc-containing powder" means that the raw material powder contains zinc-containing powder in addition to SmFeN powder, and a zinc-containing coating is formed on the surface of some or all of the SmFeN powder particles. Moreover, in this specification, unless otherwise specified, powder on which a zinc-containing coating is formed on the surface of SmFeN powder particles is sometimes referred to as "coated magnetic powder." In the manufacturing method disclosed herein, at least one of a mixed powder and a coated magnetic powder can be prepared as the raw material powder. The mixed powder is a mixture of SmFeN powder and a powder containing zinc. The coated magnetic powder is a coated magnetic powder in which a zinc-containing film is formed on the particle surface of SmFeN powder.

[0098] There are no particular limitations on the method for forming a zinc-containing film on the surface of SmFeN powder particles, but examples include methods such as rotary kiln furnaces and vapor deposition. These methods will be briefly described separately.

[0099] <Methods of using rotary kilns>

[0100] Figure 5 This is an illustrative diagram illustrating an example of a method for forming a zinc-containing film on the surface of SmFeN powder particles using a rotary kiln.

[0101] The rotary kiln 100 includes a stirring drum 110. The stirring drum 110 has a material receiving section 120, a rotating shaft 130, and a stirring plate 140. A rotating unit (not shown) such as an electric motor is connected to the rotating shaft 130.

[0102] SmFeN powder 150 and zinc-containing powder 160 are loaded into the material receiving section 120. Then, while rotating the stirring drum 110, the material receiving section 120 is heated using a heater (not shown).

[0103] If the material receiving section 120 is heated to a temperature lower than the melting point of the zinc-containing powder 160, the zinc component of the zinc-containing powder 160 undergoes solid-phase diffusion into the surface of the SmFeN powder 150 particles. As a result, a zinc-containing film is formed on the surface of the SmFeN powder 150 particles. If the material receiving section 120 is heated to a temperature above the melting point of the zinc-containing powder 160, a molten zinc-containing powder 160 is obtained. This molten powder comes into contact with the SmFeN powder 150. If the material receiving section 120 is cooled in this state, a zinc-containing film is formed on the surface of the SmFeN powder 150 particles.

[0104] The operating conditions of the rotary kiln only need to be appropriately determined to obtain the desired coating.

[0105] When the melting point of the zinc-containing powder is denoted as T, the heating temperature of the material receiving section can be, for example, above (T-50)℃, above (T-40)℃, above (T-30)℃, above (T-20)℃, above (T-10)℃, or above T℃, or below (T+50)℃, below (T+40)℃, below (T+30)℃, below (T+20)℃, or below (T+10)℃. Furthermore, when the zinc-containing powder is a powder containing metallic zinc, T is the melting point of zinc. Additionally, when the zinc-containing powder is a powder containing a zinc alloy, T is the melting point of the zinc alloy.

[0106] The rotational speed (rotational speed) of the stirring drum can be, for example, 5 rpm or more, 6 rpm or more, 10 rpm or more, or 20 rpm or more, or less than 200 rpm, 100 rpm or less, or less than 50 rpm. To prevent oxidation of the powder and the formed coating, the atmosphere during rotation is preferably an inert gas atmosphere. Inert gas atmospheres include argon atmospheres and / or nitrogen atmospheres. The rotation time of the stirring drum (coating treatment time) can be appropriately determined to form the desired zinc-containing coating. The rotation time of the stirring drum (coating treatment time) can be, for example, 1 minute or more, 5 minutes or more, 10 minutes or more, 15 minutes or more, 30 minutes or more, 45 minutes or more, or 60 minutes or more, or less than 240 minutes, less than 210 minutes, less than 180 minutes, less than 150 minutes, less than 120 minutes, or less than 90 minutes.

[0107] When a zinc-containing film is formed on the surface of SmFeN powder particles, and the particles are bonded together, the bonded particles can be pulverized. The pulverization method is not particularly limited; examples include the use of ball mills, jaw crushers, jet mills, and cutter mills, as well as combinations thereof.

[0108] [Evaporation method]

[0109] Figure 6 This is an illustrative diagram illustrating an example of a method for forming a zinc-containing film on the surface of SmFeN powder particles using a vapor deposition process.

[0110] SmFeN powder 150 is placed in a first container 181, and zinc-containing powder 160 is placed in a second container 182. The first container 181 is placed in a first heat treatment furnace 171, and the second container 182 is placed in a second heat treatment furnace 172. The first heat treatment furnace 171 and the second heat treatment furnace 172 are connected by a connecting line 173. The first heat treatment furnace 171, the second heat treatment furnace 172, and the connecting line 173 are airtight. A vacuum pump 180 is connected to the second heat treatment furnace 172.

[0111] After the pressure inside the first heat treatment furnace 171, the second heat treatment furnace 172, and the connecting passage 173 is reduced by a vacuum pump 180, their interiors are heated. As a result, zinc-containing vapor is generated from the zinc-containing powder 160 stored in the second container 182. Figure 6 As shown by the solid arrow in the image, vapor containing zinc moves from the interior of the second container 182 to the interior of the first container 181.

[0112] The zinc-containing vapor that moves into the interior of the first container 181 is cooled, thereby forming (evaporating) a film on the particle surface of the SmFeN powder 150.

[0113] By using the first container 181 as a rotating container, it can operate like a rotary kiln, further improving the coating efficiency of the film formed on the particle surface of the SmFeN powder 150. The coating efficiency will be described later.

[0114] use Figure 6 The various conditions under which the coating is formed by the method shown can be determined appropriately to obtain the desired coating.

[0115] The temperature of the first heat treatment furnace (the heating temperature of SmFeN powder) can be, for example, above 120°C, above 140°C, above 160°C, above 180°C, above 200°C, or above 220°C, or below 300°C, below 280°C, or below 260°C.

[0116] When the melting point of the zinc-containing powder is denoted as T, the temperature of the second heat treatment furnace (the heating temperature of the zinc-containing powder) can be, for example, above T℃, above (T+20)℃, above (T+40)℃, above (T+60)℃, above (T+80)℃, above (T+100)℃, or above (T+120)℃, and can be below (T+200)℃, below (T+180)℃, below (T+160)℃, or below (T+140)℃. Furthermore, when the zinc-containing powder is a powder containing metallic zinc, T is the melting point of zinc. Additionally, when the zinc-containing powder is a powder containing a zinc alloy, T is the melting point of the zinc alloy. Although a block of zinc-containing material can also be contained in the second container, from the viewpoint of rapidly melting the contents of the second container and generating zinc-containing vapor from its molten liquid, it is preferable to contain zinc-containing powder in the second container.

[0117] To promote the generation of zinc-containing vapors and prevent oxidation of powders and formed films, both the first and second heat treatment furnaces are set under reduced pressure atmospheres. The atmosphere pressure is preferably, for example, 1 × 10⁻⁶. -5 Below MPa, preferably 1×10 -6 Below MPa, and more preferably 1×10 -7 Below MPa. On the other hand, even without excessive decompression, there are no practical problems; if the aforementioned atmosphere pressure is met, the atmosphere pressure can be 1×10 MPa. -8 MPa or above.

[0118] When the first container is a rotating container, its rotation speed (rotation speed) can be, for example, 5 rpm or more, 10 rpm or more, or 20 rpm or less, or 200 rpm or less, 100 rpm or less, or 50 rpm or less.

[0119] In the vapor deposition method, after a zinc-containing film is formed on the surface of SmFeN powder particles, the aggregates of these powder particles, which are bonded together, can be pulverized. The pulverization method is not particularly limited; examples include using ball mills, jaw crushers, jet mills, screw mills, and combinations thereof.

[0120] <Zinc Coverage>

[0121] When a zinc-containing film is formed on the particle surface of SmFeN powder, a high coating ratio is preferred. This is because a high coating ratio facilitates the modification of the particle surface of the first particle group in the rare-earth magnet by the formed zinc-containing film during pressure sintering, thereby advantageously improving the coercivity. Next, the method for determining the coating ratio will be explained.

[0122] Coverage is the percentage (in percent) of zinc content that is coated on the overall surface of the particles of SmFeN powder supplied with a zinc-containing coating. Coverage (%) is calculated as follows.

[0123] Regarding the SmFeN powder after forming a zinc-containing coating, the elemental composition information of the SmFeN powder and the zinc-containing coating was obtained using X-ray photoelectron spectroscopy (XPS). The coating percentage (%) was then calculated using the following formula.

[0124] Coverage percentage (%) = [(Total compositional information of each element in the zinc-containing coating) / {(Total compositional information of each element in the SmFeN powder) + (Total compositional information of each element in the zinc-containing coating)}] × 100

[0125] When SmFeN powder is composed of, for example, Sm, Fe, and N, the sum of the compositional information of each constituent element of the SmFeN powder refers to the sum of the compositional information of each of Sm, Fe, and N. Even when SmFeN powder contains elements other than Sm, Fe, and N, the proportion of these elements is small. Therefore, even when SmFeN powder contains elements other than Sm, Fe, and N, the sum of the compositional information of each constituent element of the SmFeN powder can be approximated by the sum of the compositional information of each of Sm, Fe, and N. Furthermore, when the coating containing zinc is, for example, a metallic zinc coating, the sum of the compositional information of the coating containing zinc refers to the compositional information of Zn. When the coating containing zinc is, for example, a zinc alloy coating, the sum of the compositional information of the coating containing zinc refers to the sum of the compositional information of both Zn and the alloying elements. In the case of zinc alloys, such as Zn-Al alloys, the sum of the compositional information of each constituent element of the coating having zinc content means the sum of the compositional information of Zn and Al respectively.

[0126] For example, information about the composition of Zn refers to measuring the XPS spectrum of SmFeN powder after forming a coating with zinc composition, and determining the mass of Zn present from the peak intensities of the obtained XPS spectrum. In the case where the SmFeN powder is composed of, for example, Sm, Fe, and N, and the coating with zinc composition is, for example, a metallic zinc coating, the coverage percentage (%) is calculated as follows.

[0127] Coverage (%) = (mass of Zn present) / (total mass of Sm, Fe, N and Zn present) × 100

[0128] The coverage rate obtained in this way is preferably above 80%, above 85%, above 90%, or above 95%, and ideally 100%.

[0129] As mentioned above, a coating containing zinc typically refers to a coating containing at least one of metallic zinc and zinc alloys. When using Zn-M... 2 When referring to zinc alloys, M 2 Elements that alloy with Zn (zinc) to lower the melting point of the zinc alloy to the melting point of Zn, as well as unavoidable impurity elements, can be selected. This improves sinterability during the pressure sintering process. M is used to adjust the melting point of the zinc alloy to be lower than the melting point of Zn. 2 Elements that form eutectic alloys with Zn can be listed, such as M. 2Typical examples include Sn, Mg, and Al, as well as combinations thereof. Sn is tin, Mg is magnesium, and Al is aluminum. Elements that do not impair the melting point reduction effect of these elements, or the properties of the product, can also be selected as M. 2 In addition, the so-called unavoidable impurity elements refer to impurities and other impurities contained in the raw materials of zinc-containing powder that cannot be avoided, or whose presence would lead to a significant increase in manufacturing costs.

[0130] Using Zn-M 2 In the zinc alloy represented, Zn and M 2 The ratio (molar ratio) only needs to be appropriately determined to make the pressure sintering temperature suitable. 2 The molar ratio relative to the total zinc alloy can be, for example, 0.05 or more, 0.10 or more, or 0.20 or more, or 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, or 0.30 or less.

[0131] The zinc-containing powder used in the aforementioned "method using a rotary kiln" and "evaporation method" may, in addition to metallic zinc and / or zinc alloys, contain substances with binder and / or modifier functions, as well as other functions, without impairing the effects of the present invention. Examples of other functions include, for instance, improved corrosion resistance.

[0132] Even when a zinc-containing film is formed on the surface of the SmFeN powder particles in the raw material powder, the zinc content in the raw material powder follows the same proportion as when the raw material powder contains zinc-containing powder in addition to SmFeN powder. When the formation of the zinc-containing film and the use of zinc-containing powder are combined, the zinc content in the raw material powder is the combined proportion of zinc content derived from the zinc-containing film and zinc content derived from the zinc-containing powder.

[0133] <Pressure sintering process>

[0134] The raw material powder is subjected to pressure sintering. Before pressure sintering, a magnetic field is applied to the raw material powder to impart magnetic orientation to the SmFeN powder in the raw material powder. Moreover, the magnetic field is maintained on the raw material powder until at least during the pressure sintering process, preferably until the pressure sintering is completed. As a result, the SmFeN powder in the sintered body is sufficiently oriented, thereby imparting sufficient anisotropy to the sintered body (rare earth magnet).

[0135] As mentioned above, if a magnetic field can be applied to the raw material powder, there are no particular limitations on the method of applying the magnetic field, but the preferred method of applying the magnetic field will be described below.

[0136] <Methods for Applying a Magnetic Field>

[0137] Figure 7 This is an illustrative diagram showing one example of a method of applying a magnetic field, but it is not limited to this. Figure 7 In the method shown, a magnetic field source 30 is positioned around the SmFeN powder 10. The SmFeN powder 10 may contain particles of zinc-containing powder, or a zinc-containing film may be formed on the surface of the SmFeN powder particles, or a combination of both. In other words, the magnetic field source 30 can be positioned around the raw material powder. The dashed line indicates the magnetic field applied to the SmFeN powder.

[0138] The applied magnetic field can be, for example, above 500 kA / m, above 1000 kA / m, above 1500 kA / m, or above 1600 kA / m, or below 20000 kA / m, below 15000 kA / m, below 10000 kA / m, below 5000 kA / m, below 3000 kA / m, or below 2000 kA / m.

[0139] Examples of magnetic field sources 30 include electromagnetic coils and permanent magnets. They can also be used in combination. This combination will be described in detail later. In the manufacturing method of this disclosure, a magnetic field is also applied during pressure sintering. During pressure sintering, the raw material powder needs to be heated and pressurized, thus the pressure sintering apparatus tends to be complex and large-scale. Therefore, from the viewpoint of simplifying the structure surrounding the pressure sintering apparatus, a permanent magnet is preferred as the magnetic field source.

[0140] When using an electromagnetic coil as the magnetic field generator 30, a static magnetic field or an alternating pulsed magnetic field can be applied.

[0141] When using a permanent magnet as the magnetic field source 30, examples of permanent magnets include alnico magnets, ferrite magnets, and rare-earth magnets. From the viewpoint of miniaturizing the installation space while applying a strong magnetic field, rare-earth magnets are preferred. Examples of rare-earth magnets include samarium-cobalt magnets (Sm-Co magnets) and neodymium magnets (Nd-Fe-B magnets). The raw material powder and its surroundings are at a relatively low temperature at the beginning of pressure sintering, but gradually become high-temperature. Therefore, from the viewpoint of applying a magnetic field to the raw material powder for as long as possible during pressure sintering, it is preferable to use a samarium-cobalt magnet with a high Curie temperature. Alternatively, a soft magnetic material can be placed near the permanent magnet to increase the applied magnetic field. Examples of soft magnetic materials include permalloy, silicon steel sheet, and permendur. They can also be combined. From the viewpoint of increasing the applied magnetic field, permendur is preferred. The term "nearby" refers to a location that can increase the magnetic field emitted by a permanent magnet.

[0142] As an example, the case where an electromagnetic coil and a permanent magnet are used as the magnetic field source 30 can be represented as follows. Figure 7 A permanent magnet is positioned at the location of the magnetic field source 30 before magnetization. An electromagnetic coil is further positioned outside the permanent magnet, and a magnetic field is applied to both the permanent magnet and the SmFeN powder 10 using the electromagnetic coil. Thus, the permanent magnet is magnetized by the magnetic field applied by the electromagnetic coil, and the particles of the SmFeN powder 10 are individually oriented. If the application of the magnetic field by the electromagnetic coil begins before pressure sintering, the magnetic field can continue to be applied to the SmFeN powder 10 through the magnetized permanent magnet even if the application of the magnetic field by the electromagnetic coil is stopped before pressure sintering.

[0143] To suppress the oxidation of the raw material powder, it is preferable to apply a magnetic field in an inert gas atmosphere. The inert gas atmosphere includes an argon atmosphere and / or a nitrogen atmosphere.

[0144] <Direction of magnetic field application>

[0145] There are no particular restrictions on the direction in which the magnetic field is applied, but it is preferable to apply the magnetic field in a direction different from the pressure direction of pressure sintering. The rationale is explained using the accompanying drawings. Figure 8 This is an illustrative diagram showing an example of the direction in which a magnetic field is applied. In Figure 8 In the diagram, the dashed arrows indicate the direction of the magnetic field applied to the SmFeN powder 10, while the hollow arrows indicate the direction of pressure sintering. The phrase "applying a magnetic field in a direction different from the pressure direction of pressure sintering" means... Figure 8 The case where the angle θ formed by the direction of applying pressure and the direction of applying the magnetic field (where 0°≤θ≤90°) is not 0°. Figure 8 In this process, there may be particles of powder containing zinc between the particles of SmFeN powder 10, a film containing zinc may be formed on the surface of the particles of SmFeN powder, or a combination of the two (the above two cases) may be used.

[0146] As described above, in magnetically oriented SmFeN powder, the entire SmFeN powder forms a rod-shaped permanent magnet. In this case, if no magnetic field is applied to the SmFeN powder, then... Figure 3 As shown, the magnetic orientation of each particle in the SmFeN powder collapses due to the magnetic field, indicated by the dashed line. On the other hand, in the manufacturing method of this disclosure, since a continuous magnetic field is applied until at least during pressure sintering, this is easily counteracted. Figure 3 The magnetic field, represented by a dashed line, indicates that each particle of the SmFeN powder can maintain its magnetic orientation. However, even if the aforementioned magnetic field is not completely canceled out, Figure 3 A portion of the magnetic field, represented by a dashed line, remains in the powder. Even when a magnetic field is applied in a direction different from the pressure direction during pressure sintering, it can advantageously suppress the collapse of magnetic orientation. Although not bound by theory, this is believed to be due to the following reason: In SmFeN powder, the particles are close together. In this state, if pressure is applied to the SmFeN powder, the particles tend to flow in a direction different from the pressure direction. This is believed to be because: if a magnetic field is applied in the direction in which the particles tend to flow, i.e., in a direction different from the pressure direction, the particles flow while simultaneously orienting (rotating) towards the magnetic field.

[0147] From the viewpoint of suppressing the rotation of SmFeN powder particles, θ is preferably 10° or more, 20° or more, or 30° or more, more preferably 40° or more, 50° or more, or 60° or more, even more preferably 70° or more, 75° or more, 80° or more, or 85° or more, and most preferably 90°.

[0148] <Methods and conditions for pressure sintering>

[0149] If the requirements for magnetic field application described above are met, the pressure sintering method is not particularly limited, and known methods can be applied. Examples of pressure sintering methods include: preparing a mold with a cavity and a punch that can slide inside the cavity; loading raw material powder into the cavity; and sintering the raw material powder while applying pressure to the powder using the punch. In this method, typically, a high-frequency induction coil is used to heat the mold and / or the cavity. Alternatively, plasma discharge sintering (SPS) can also be used.

[0150] As long as the pressure sintering temperature, pressure, and time are appropriately determined to prevent the magnetic phase of the SmFeN powder in the raw material powder from decomposing, a sintered body can be obtained. Furthermore, in the following description, the pressure sintering temperature, pressure, and time will sometimes be referred to simply as sintering temperature, sintering pressure, and sintering time.

[0151] If the sintering temperature is 300°C or higher, the SmFeN powder particles can be bonded together. In the following description, the case where the raw material powder contains zinc powder in addition to SmFeN powder, and / or where a zinc-containing film is formed on the surface of the SmFeN powder particles, is sometimes referred to as "the raw material powder containing zinc." When the raw material powder contains zinc, if the sintering temperature is 300°C or higher, a portion of the Fe and zinc components on the surface of the SmFeN powder particles interdiffusion occurs, increasing the bonding force between the SmFeN powder particles. The interdiffusion of Fe and zinc components on the surface of the SmFeN powder particles can be solid-phase diffusion or liquid-phase diffusion. From the viewpoint of bonding between the SmFeN powder particles, the sintering temperature can be, for example, 310°C or higher, 320°C or higher, 340°C or higher, or 350°C or higher.

[0152] On the other hand, if the sintering temperature is below 500°C, 470°C, or 450°C, the decomposition of the magnetic phase in the SmFeN powder can be avoided. When the raw material powder contains zinc, if the sintering temperature is below 430°C, 420°C, 410°C, 400°C, 390°C, 380°C, 370°C, or 360°C, excessive interdiffusion of Fe on the particle surface of the SmFeN powder and zinc in the modified material powder can be avoided.

[0153] Regarding sintering pressure, any sintering pressure that can increase the density of the sintered body can be selected. Typical sintering pressures can be above 100 MPa, above 200 MPa, above 400 MPa, above 500 MPa, above 600 MPa, above 800 MPa, or above 1000 MPa, or below 2000 MPa, below 1800 MPa, below 1600 MPa, below 1500 MPa, below 1300 MPa, or below 1200 MPa.

[0154] The sintering time only needs to be appropriately determined to obtain a sintered body. The sintering time does not include the heating time until the heat treatment temperature is reached. Sintering times can be, for example, more than 1 minute, more than 2 minutes, or more than 3 minutes, or less than 60 minutes, 50 minutes, 40 minutes, 30 minutes, 20 minutes, 10 minutes, or 5 minutes. When the raw material powder contains zinc, the sintering time can be shortened, and the sintering time can be less than 30 minutes, 20 minutes, 10 minutes, or 5 minutes.

[0155] After the sintering time has elapsed, the sintered body is cooled, and the sintering process is complete. A rapid cooling rate can suppress oxidation of the sintered body. The cooling rate can be, for example, 0.5–200 °C / second.

[0156] For the atmosphere in pressure sintering, an inert gas atmosphere is preferred to suppress oxidation of the raw material powder and the sintered body. Inert gas atmospheres include argon and / or nitrogen atmospheres. Alternatively, sintering can be carried out in a vacuum.

[0157] Alternatively, the raw material powder can be pre-compressed to form a pressed powder body before pressure sintering. Then, the pressed powder body is subjected to pressure sintering. As explained so far, the manufacturing method of this disclosure applies a magnetic field to the raw material powder to impart magnetic orientation, and maintains the magnetic orientation by continuously applying the magnetic field until at least during pressure sintering. Therefore, when the raw material powder is pre-compressed before pressure sintering, the pressed powder body can be formed by compressing the raw material powder while applying a magnetic field. In this specification, unless otherwise specified, the formation of such a pressed powder body is sometimes referred to as "forming in a magnetic field." Forming in a magnetic field will be described in detail below.

[0158] <Shaping in a magnetic field>

[0159] By forming the powder in a magnetic field, the particles of SmFeN powder in the pressed powder can be individually oriented. If such pressed powder is then subjected to pressure sintering, anisotropy can be imparted to the sintered body (rare earth magnet), thereby increasing remanent magnetization.

[0160] Forming methods in a magnetic field can be well-known methods, such as compressing raw material powder using a forming mold with a magnetic field source positioned around it. The forming pressure can be, for example, 10 MPa or more, 20 MPa or more, 30 MPa or more, 50 MPa or more, 100 MPa or more, or 150 MPa or more, or 1500 MPa or less, 1000 MPa or less, or 500 MPa or less. The time for applying the above forming pressure can be, for example, 0.5 minutes or more, 1 minute or more, or 3 minutes or more, or 10 minutes or less, 7 minutes or less, or 5 minutes or less. The applied magnetic field can be, for example, above 500 kA / m, above 1000 kA / m, above 1500 kA / m, or above 1600 kA / m, or below 20000 kA / m, below 15000 kA / m, below 10000 kA / m, below 5000 kA / m, below 3000 kA / m, or below 2000 kA / m.

[0161] As sources of magnetic fields, examples include electromagnetic coils and permanent magnets, and they can also be used in combination.

[0162] When using an electromagnetic coil as a magnetic field source, a static magnetic field or an alternating pulsed magnetic field can be applied.

[0163] When using permanent magnets as the magnetic field source, examples of permanent magnets include AlNiCo magnets, ferrite magnets, and rare-earth magnets. From the viewpoint of miniaturizing the installation space while applying a strong magnetic field, rare-earth magnets are preferred. Examples of rare-earth magnets include samarium-cobalt magnets and neodymium magnets. Alternatively, soft magnetic materials can be placed near the permanent magnet to increase the applied magnetic field. Examples of soft magnetic materials include permalloy, silicon steel sheets, and bermington alloys. Combinations of these materials are also possible. From the viewpoint of increasing the applied magnetic field, bermington alloys are preferred. "Near" refers to a location where the magnetic field emitted by the permanent magnet can be increased.

[0164] One example of using both an electromagnetic coil and a permanent magnet as the magnetic field source is as follows: A permanent magnet is placed around the SmFeN powder before magnetization. An electromagnetic coil is further placed outside the permanent magnet, and a magnetic field is applied to both the permanent magnet and the SmFeN powder using the electromagnetic coil. Thus, the permanent magnet is magnetized by the magnetic field applied by the electromagnetic coil, and the SmFeN powder particles are individually oriented.

[0165] There are no particular restrictions on the direction of the applied magnetic field. From the viewpoint of advantageously orienting the SmFeN powder in the compressed powder, it is preferable to apply the magnetic field in a direction different from the compression forming direction, similar to the case of pressure sintering. The angle formed by the compression forming direction and the direction of the applied magnetic field can follow the aforementioned θ.

[0166] To suppress oxidation of the mixed powder, magnetic field forming is preferably performed in an inert gas atmosphere. Inert gas atmospheres include argon and / or nitrogen atmospheres.

[0167] Deformation

[0168] In addition to the content described above, the manufacturing method disclosed herein can be modified in various ways within the scope of the claims.

[0169] For example, the sintered body obtained by pressurizing and sintering the raw material powder can also be heat-treated. Heat treatment allows the SmFeN powder particles to bond more firmly together and promotes modification. In cases where the SmFeN powder contains microparticles, it also promotes their neutralization.

[0170] The heat treatment temperature can be, for example, above 350°C, above 360°C, above 370°C, or above 380°C, or below 410°C, below 400°C, or below 390°C. The heat treatment time can be above 3 hours, above 4 hours, above 5 hours, above 8 hours, above 10 hours, above 12 hours, above 15 hours, above 17 hours, or above 20 hours, or below 40 hours, below 35 hours, below 30 hours, below 25 hours, or below 24 hours. To suppress oxidation of the sintered body, it is preferable to perform the heat treatment in a vacuum or in an inert gas atmosphere, including an argon atmosphere and / or a nitrogen atmosphere.

[0171] Example

[0172] The manufacturing method of this disclosure is described in more detail below through examples and comparative examples. Furthermore, the manufacturing method of rare earth magnets of this disclosure is not limited by the conditions used in the following examples.

[0173] Sample preparation

[0174] The samples of Examples 1-2 and Comparative Examples 1-3 were prepared according to the following guidelines.

[0175] <Example 1>

[0176] SmFeN powder and zinc-containing powder were prepared. The SmFeN powder used was a commercially available product (Z21 manufactured by Nichia Chemical Co., Ltd.). The D of the SmFeN powder... 50 The particle size is 3.08 μm. The powder containing zinc is metallic zinc powder with a purity of 99.9% by mass. Additionally, the D of the metallic zinc powder... 50 It is 0.5μm.

[0177] SmFeN powder and zinc-containing powder are mixed to obtain raw material powder. The proportion of zinc content relative to the total raw material powder, i.e., the mixing ratio of zinc-containing powder, is 10% by mass.

[0178] Raw material powder is loaded into the mold cavity of the forming mold, and then, as... Figure 7 As shown, neodymium magnets are placed inside the mold cavity as permanent magnets before magnetization. An electromagnetic coil is used to apply a magnetic field to the raw material powder and the neodymium magnets for 1 minute. After the neodymium magnets are magnetized, the application of the magnetic field using the electromagnetic coil is stopped. Then, the raw material powder is subjected to pressure sintering. The angle θ formed by the pressure direction of the pressure sintering and the direction of the magnetic field applied by the electromagnetic coil is approximately 90°.

[0179] The method of applying the magnetic field using an electromagnetic coil and the magnitude of the magnetic field are shown in Table 1. Furthermore, in Table 1, the case where "forming pressure in the magnetic field" is marked as "-" indicates that no pressure was applied to the raw material powder until the start of pressure sintering. The loading of the raw material into the forming mold and the application of the magnetic field using the electromagnetic coil were performed in a nitrogen atmosphere. Pressure sintering was performed in an argon atmosphere, and the various conditions for pressure sintering are shown in Table 1. Additionally, no AC demagnetization was performed throughout the entire process. The sintered body thus obtained was used as the sample for Example 1.

[0180] <Example 2>

[0181] Except that the permanent magnet before magnetization was a samarium-cobalt magnet, the process was carried out in the same manner as in Example 1 to obtain the sample of Example 2.

[0182] <Comparative Example 1>

[0183] Except that no permanent magnet was placed inside the forming mold, the process was the same as in Example 1, thus preparing the sample for Example 2. Furthermore, the application of the magnetic field using an electromagnetic coil was stopped before the start of pressure sintering.

[0184] <Comparative Example 2>

[0185] No permanent magnet was placed inside the forming mold, and a static magnetic field was applied. The powder was pre-formed in the magnetic field before pressure sintering, and then subjected to AC demagnetization. The demagnetized powder was then subjected to pressure sintering. Otherwise, the process was the same as in Example 1, thus preparing the sample for Comparative Example 2. The forming pressure in the magnetic field was 50 MPa. Furthermore, the application of the magnetic field using an electromagnetic coil was stopped before AC demagnetization.

[0186] <Comparative Example 3>

[0187] No permanent magnet was placed in the forming mold, and a static magnetic field was applied. The pressed powder was formed in the magnetic field before pressure sintering. Then, the pressed powder was pressure sintered. Otherwise, it was carried out in the same way as in Example 1, thereby preparing the sample of Comparative Example 3.

[0188] evaluate

[0189] The magnetic properties of each specimen were measured. The magnetic properties were measured at room temperature using a vibrating specimen magnetometer (VSM). The degree of orientation was calculated using the method described above.

[0190] The evaluation results are shown in Table 1, "Magnetic Properties". Table 1 confirms that a good orientation degree of 0.95 or higher was obtained in the samples of Examples 1 and 2. In Examples 1 and 2, since a permanent magnet was placed in the mold cavity of the forming mold, even after the application of the magnetic field using the electromagnetic coil ceased, the magnetized permanent magnet could continue to apply a magnetic field to the raw material powder until at least during the pressure sintering process. As a result, it is considered that the magnetic orientation of the SmFeN powder in the raw material powder could be maintained.

[0191] On the other hand, Table 1 confirms that good orientation was not obtained in the samples of Comparative Example 1 and Comparative Example 3. In Comparative Example 1 and Comparative Example 3, since no permanent magnet was placed in the mold cavity of the molding die, no magnetic field was applied to the SmFeN powder of the raw material powder from the outside after the application of the magnetic field using the electromagnetic coil ceased. Therefore, it is believed that even if the SmFeN powder in the raw material powder is temporarily oriented due to the application of the magnetic field using the electromagnetic coil, the magnetic field formed by the entire SmFeN powder of the raw material powder will cause its orientation to collapse.

[0192] Furthermore, Table 1 confirms that in Comparative Example 2, although no permanent magnet was placed in the mold cavity of the molding die, a relatively good orientation was still obtained. This is believed to be because, in Comparative Example 2, after the application of the magnetic field using the electromagnetic coil was stopped, the residual magnetism in the SmFeN powder was removed by AC demagnetization. As a result, it was difficult for the entire SmFeN powder in the raw material powder to form a magnetic field, and therefore the SmFeN powder in the raw material powder, which was temporarily oriented by the application of the magnetic field using the electromagnetic coil, was easier to maintain its orientation. However, compared with the samples of Examples 1 and 2, the orientation of the sample of Comparative Example 2 was slightly worse. Even with AC demagnetization, it was difficult to completely remove the residual magnetism in the SmFeN powder in the raw material powder. Even if the residual magnetism in the SmFeN powder in the raw material powder could be completely removed by AC demagnetization, a magnetic field formed by the entire SmFeN powder would still occur until the removal of the magnetism, albeit small. Therefore, it is believed that even if the SmFeN powder in the raw material powder was temporarily oriented by the application of the magnetic field using the electromagnetic coil, its orientation would slightly collapse.

[0193] The above results confirm the effectiveness of the manufacturing method disclosed herein.

[0194]

Claims

1. A method for manufacturing a rare earth magnet, comprising the following steps: Prepare a raw material powder containing magnetic powder, wherein the magnetic powder contains Sm, Fe and N and has at least a portion of Th2Zn. 17 Type and Th2Ni 17 A magnetic phase with at least one crystal structure of the type is formed on the particle surface of the magnetic powder with a zinc composition; and Before pressure sintering, the raw material powder is compressed and shaped into a pressed powder body while applying a magnetic field to impart magnetic orientation. The magnitude of the applied magnetic field is above 500 kA / m and below 20000 kA / m. The compressed powder is subjected to pressure sintering, and... The magnetic field is continuously applied to maintain the magnetic orientation until the pressure sintering is completed, and The magnetic field is applied in a direction different from the pressure direction of the pressure sintering. After the sintering time has elapsed, the sintered body is cooled to end the sintering process. The cooling rate is 0.5~200℃ / second.

2. The method for manufacturing rare earth magnets according to claim 1, wherein the magnetic field is applied in a direction perpendicular to the pressure direction of the pressure sintering.

3. The method for manufacturing a rare earth magnet according to claim 1 or 2, wherein a permanent magnet is used to apply the magnetic field.

Citation Information

Patent Citations

  • Magnetic field molding method

    JP2021141121A

  • Method for manufacturing rare earth magnetic mold

    WO2015199096A1